Multi-Tunnel Triboelectric Nanogenerator for Scavenging Mechanical Energy in Marine Floating Bodies - Ziyi Zhang; Zhiyuan Hu; Yan Wang; Yawei Wang; Qiqi Zhang; Dehua Liu; Hao Wang; Minyi Xu (Journal of Marine Science and Engineering, 2022)
The ocean has an abundant reserve of wave energy, which is considered to be a clean, widely distributed and inexhaustible resource. Triboelectric nanogenerators (TENGs) have been regarded as a reliable technology for harvesting wave energy due to its robustness and efficiency in scavenging random mechanical energy. In this study, a wave energy harvesting multi-tunnel TENG (MT-TENG) has been proposed, which could be integrated easily with ocean buoys. The MT-TENG consists of polytetrafluoroethylene (PTFE) balls and a multi-tunnel frame, which could convert wave energy into electrical energy. The multi-tunnel design also avoids possible mutual obstruction of the PFTE balls during the movement. Compared with the flat type structure, the multi-tunnel structure could enhance output performance obviously. With an agitation frequency of 2 Hz and vibration amplitude of 130 mm, the MT-TENG has a peak power density of 8.3 W/m3, which is five times that of the flat type structure TENG. By integrating with a life buoy and floating pipe line, the MT-TENG could harvest wave energy to light LEDs continuously, which could provide a new solution for maritime rescue and night offshore oil delivery warning.